Assessing the oncolytic potential of reovirus reassortants - Major, Jennifer Rosmarie (University of Ottawa (Canada), 2007)
Type 3 Dearing (T3D) reovirus is an oncolytic virus able to lyse a majority of tumor types. The major drawback is that ∼20% of tumor types are resistant to lysis by T3D and therefore there is a need to improve the oncolytic ability of reovirus to include resistant tumors. When designing an oncolytic virus, an ideal virus would be sensitive to double stranded protein kinase (PKR) pathway involved in the anti-viral response of normal cells. Previous studies in our lab determined which gene segments were involved in generating high viral yields in the absence of PKR. The M1 gene segment from T3D controls PKR sensitivity and the Type 1 Lange (T1L) L3 gene segment controlled the increased viral yield in the absence of PKR. The hypothesis of this study is that improved oncolysis can be achieved by combining the T1L L3 gene segment with the T3D MI gene segment through the creation of T1L x T3D reassortants. The reassortant viruses with these gene segments and other unidentified gene segment combinations have the potential to have superior oncolytic ability compared to the parent serotypes. The Balb/c murine colon carcinoma tumor cell line, CT26, is resistant to lysis by serotype 1 Lang (T1L) and T3D following infection in vitro and is thus a demanding model in which to screen T1L x T3D reassortants for improved oncolytic ability. To identify genes involved in viral growth and protein synthesis a panel of T1L x T3D reassortants was monitored for replication and protein synthesis in CT26 cells as well as mouse embryo fibroblasts from wt and the PKR knockout (PKR-/-) Balb-c mice. In epithelial cells the primary gene segment involved in viral yield and protein production in CT26 cells was the T3D S1 gene segment, with secondary contribution from T3D L2, M2 and M3 gene segments for viral yield, and T3D L1 and M2 gene segments for protein production. However, in fibroblasts the T1L L3 gene segment was important for protein production in the presence of PKR and the T1L L1 and T3D M2 genes segments were involved in protein production in the absence of PKR. Different reovirus genes are involved in the productivity and permissiveness of infection in different cell types. In contrast to in vitro infection, 4 T1L x T3D reassortants, E1388, E1386, E1397, and EB123, possess enhanced ability to prolong survival of Balb/c mice bearing CT26 lung metastases. This finding demonstrated that ability to lyse tumors does not correlate with ability to lyse cells in vitro and that specific reovirus reassortants possess enhanced oncolytic properties. Virus infection of CT26 tumors in vivo with EB88, EB86, EB97, and EB123 was measured by immunofluorescence with anti-reovirus serum as well as apoptosis over 7 days following infection to show that all reassortants with enhanced oncolytic properties had infections of longer duration and generally more extensive TUNEL positive cells. I also observed that PKR-/- mice had a unique pattern of infection relative to T1L and T3D; bronchiolar epithelium was infected with T3D but not with T1L, whereas bronchiolar epithelium of wt Balb-c mice was resistant to infection with both viruses. The PKR dependent bronchiolar epithelial tropism mapped to the S1 genome segment. This finding, which contrasts with previous mapping of PKR dependent tropism for fibroblasts to the M1 genome segments, has identified a tissue specific aspect to the PKR dependent control of infection with reoviruses. As >95% of tumors are epithelial in origin, the difference in PKR dependent infection between fibroblast and epithelium is of relevance to oncolytic viruses which are thought to exploit defects in interferon responsiveness in tumor cells, which are largely epithelial in origin. On assessing the genotypes of reassortants that possess enhanced oncolytic abilities the T3D-L2 and T3D-M1 genome segments plus T1L-L3 and T1L-M2 genome segments appeared to be functioning to enhance tumor destruction through modulation of cell growth and protein production (L2 and L3-enhanced growth), and interferon/PKR sensitivity (M1-enhanced sensitivity). Although oncolytic properties appear multigenically controlled it is possible to obtain reovirus reassortants with enhanced combinations of proprieties that favor improved abilities to destroy tumors in intact host organisms. This study is thus foundational and has provided important data for further analysis of the mechanisms of reovirus tumor attack and its application to therapy.
Keywords: Biology, Microbiology.; Biology, Virology.